Giving behavior of millionaires - Smeets, Paul; Bauer, Rob; Gneezy, Uri (Proceedings of the National Academy of Sciences - PNAS, 2015)
This paper studies conditions influencing the generosity of wealthy people. We conduct incentivized experiments with individuals who have at least €1 million in their bank account. The results show that millionaires are more generous toward low-income individuals in a giving situation when the other participant has no power, than in a strategic setting, where the other participant can punish unfair behavior. Moreover, the level of giving by millionaires is higher than in any other previous study. Our findings have important implications for charities and financial institutions that deal with wealthy individuals.